Identification of a large-effect QTL associated with kernel discoloration in barley. (November 2018) - Romero, Cynara C.T.; Vels, Anton; Niks, Rients E.
Abstract: Three barley mapping populations sharing the parental line SusPtrit suffered from an unknown condition affecting grain quality and germination. Grains showed dark blotches or even whole-grain discoloration and shrivelling. Symptoms were similar to kernel discoloration as reported in wheat and barley. Some covered-seed lines affected by this quality condition produced grains that were either not covered at all or in which partial hull loss was observed, a phenotype that resembles that of grain skinning. No fungal or bacterial agent was identified as causal organism, and we demonstrate that the poor quality phenotype is not transmitted to the next generation – therefore unlikely due to a seed borne pathogen. A major effect QTL on chromosome 6H was mapped independently in all three populations, with the poor quality allele contributed by SusPtrit. A second, minor effect QTL, was mapped on chromosome 2H in the SusPtrit x Golden Promise population, with Golden Promise as the parent donor of the allele conferring poor quality. The grain quality disorder is not linked to the nud gene on chromosome 7H for the naked/covered seed trait. Highlights: A major effect QTL on 6H is associated with a condition affecting barley grains. The poor grain quality phenotype is contributed by the experimental line SusPtrit. No fungal or bacterial agent was identified as causal organism. Extra fertilizer input does not help improving grain quality. Hulled barley lines affected show a phenotype that resembles grain skinning.